PHONETIC REHABILITATION FOR REMOVABLE DENTAL PROSTHETICS - M. Nidzelsky; V. Chikor; N. Tsvetkova (Український стоматологічний альманах, 2019)
Removable prosthesis is considered as a device with therapeutic, rehab and prophylactic functions, which allows to improve the quality of life of the dentist. Its use is always aimed at solving three problems: restoration of chewing; restoration of pronunciation of sounds; restoration of aesthetic norms of a person.